The Parameters Basis of the Protective Sheller of the Longitudinal Pawl Making Device Between Cotton Rows - Murtazoev Azizbek Nusrat ugli; Juraev Akram Azamat ugli; Safarov Shavkat Tuxta ugli; Safarov Husniddin Sirojiddin ugli (Genius Journals, 2022)
The article describes the results of research on the parameters of the sheath that protects the longitudinal pawl formation device between cotton rows from burying cotton seedlings in the soil pile.
Keywords: Cotton; Longitudinal Pawl; Aggregate; Frame